City of speed - London, Alex (London, Alex. Battle dragons, 2022)
"In a modern mega-city built around dragons, one boy gets caught up in the world of underground dragon battles and a high-stakes gang war that could tear his family apart. In the city of Drakopolis, dragons and humans have co-existed for centuries. Dragons burn the city's garbage, taxi its busy citizens from place to place, and even compete in vicious underground battles for ganglike kins. But the dragons also compete in legal sports, like the spectacular aerial races that draw in cheering crowds by the tens of thousands. Abel is at just such a race when he witnesses the unthinkable. A long-shot competitor pulls off an impossible win -- then flies into a destructive rage! Someone in the city is experimenting on dragons: hacking their DNA, rebuilding their bodies, and breaking their minds. Who could be driving the dragons berserk? Abel must find out who's behind the experiments and put a stop to them, and to do so he'll infiltrate the kins' underground street races on a long-shot dragon of his own. But with his sister working for a kin, his brother serving the city's secret police, and a bully at school racing for Abel's worst enemies, will Abel find any safety past the finish line?"--